The roles and values of the natural environment in Northern Uganda’s peace process: a conceptual document analysis - Nardi, Maria Andrea;; Kasznar, Alice (Resilience Alliance., 2025)
Over the past years, the natural environment has increasingly become instrumental in peace policies and the focus of study in peace and conflict research. Concurrently, there is mounting global recognition that nature contributes to peoples wellbeing in manifold ways and that incorporating diverse values of nature in policymaking is paramount for sustainable development. At the nexus of current debates on environmental peacebuilding and nature values and contributions to people, the aim of this study is to understand how peace narratives in Northern Uganda have integrated environmental considerations and accommodated diverse understandings and values of nature to reflect on prospects for sustainable peace. Even though the armed conflict between the Lord Resistance Army and the Government of Uganda in Northern Uganda was not a conflict for access and control over natural resources per se, twenty years of conflict have affected the natural environment as well as social-ecological relations between local peoples and nature. Informed by our theoretical approach from political ecology, we carry out a descriptive and conceptual document analysis using an analytical framework based on three types of values of nature: (a) instrumental, when nature is valued as an instrument or means to an end, (b) intrinsic, when nature is valued in itself, and (c) relational, when nature is valued as the social-ecological relations that it nurtures among people and people and nature. Our central argument is that for peace to be sustainable, understandings and values stemming from peoples directly affected by armed conflicts and dependent on their natural environment should permeate peace narratives and strategies. In particular, relational values of nature become central for nurturing relations, regulating conflict, and eventually assisting the possibilities for long-lasting peace.